Comparative Diagnostic Accuracy of Low-Dose CT Kub and Conventional CT in Detecting Renal and Ureteric Calculi - Marya Anwar, Slaohouddin Asadullah, Sadia Ashraf, Mehwish Imtiaz, Nabeela Awan, Fatima Khawar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Computed Tomography (CT) KUB is the imaging modality of choice for detecting renal and ureteric calculi due to its high sensitivity and specificity. However, conventional CT involves substantial radiation exposure. Objective: To compare the diagnostic accuracy of low-dose CT KUB with conventional CT KUB in detecting renal and ureteric calculi, and to evaluate its performance across different patient subgroups. Methods: This prospective, observational study was conducted at Punjab Rangers Teaching Hospital, Lahore from 5 Feb 2023 to 10 August 2023. A total of 85 patients with clinical suspicion of urolithiasis were recruited for the study. These patients presented with symptoms such as acute flank pain, hematuria, or a known history of renal calculi. All patients provided informed written consent before participation. Results: Low-dose CT detected renal or ureteric calculi with a sensitivity of 95.6%, specificity of 92.6%, PPV of 97.0%, NPV of 89.3%, and overall diagnostic accuracy of 94.7%. The mean radiation dose was 2.1 mSv for low-dose CT versus 8.9 mSv for standard-dose CT, representing a 76% dose reduction (p < 0.001). Diagnostic performance was highest for stones ≥4 mm and remained acceptable across different BMI categories and stone locations. Interobserver agreement for low-dose CT was strong (κ = 0.88). Conclusion: Low-dose CT KUB offers comparable diagnostic performance to standard-dose CT while significantly reducing radiation exposure. It is a reliable and safer alternative for the evaluation of suspected urolithiasis, particularly in young patients and those requiring frequent imaging. Keywords: Low-dose CT, CT KUB, urolithiasis, renal calculi, ureteric stones, diagnosis.